Significant decrease of maternal mitochondria carryover using optimized spindle-chromosomal complex transfer - Liao, Xiaoyu; Li, Wenzhi; Lin, Kaibo; Jin, Wei; Zhang, Shaozhen; Wang, Yao; Ma, Meng; Xie, Yating; Yu, Weina; Yan, Zhiguang; Gao, Hongyuan; Zhao, Leiwen; et al. (PLoS biology, 2023)
Mutations in mitochondrial DNA (mtDNA) contribute to a variety of serious multi-organ human diseases, which are strictly inherited from the maternal germline. However, there is currently no curative treatment. Attention has been focused on preventing the transmission of mitochondrial diseases through mitochondrial replacement (MR) therapy, but levels of mutant mtDNA can often unexpectedly undergo significant changes known as mitochondrial genetic drift. Here, we proposed a novel strategy to perform spindle-chromosomal complex transfer (SCCT) with maximal residue removal (MRR) in metaphase II (MII) oocytes, thus hopefully eliminated the transmission of mtDNA diseases. With the MRR procedure, we initially investigated the proportions of mtDNA copy numbers in isolated karyoplasts to those of individual oocytes. Spindle-chromosomal morphology and copy number variation (CNV) analysis also confirmed the safety of this method. Then, we reconstructed oocytes by MRR-SCCT, which well developed to blastocysts with minimal mtDNA residue and normal chromosomal copy numbers. Meanwhile, we optimized the manipulation order between intracytoplasmic sperm injection (ICSI) and SCC transfer and concluded that ICSI-then-transfer was conducive to avoid premature activation of reconstructed oocytes in favor of normal fertilization. Offspring of mice generated by embryos transplantation in vivo and embryonic stem cells derivation further presented evidences for competitive development competence and stable mtDNA carryover without genetic drift. Importantly, we also successfully accomplished SCCT in human MII oocytes resulting in tiny mtDNA residue and excellent embryo development through MRR manipulation. Taken together, our preclinical mouse and human models of the MRR-SCCT strategy not only demonstrated efficient residue removal but also high compatibility with normal embryo development, thus could potentially be served as a feasible clinical treatment to prevent the transmission of inherited mtDNA diseases.